Determinants of Importation and Deprivation Models on Committed Juvenile Offenders' Violent Misconduct: A Taiwanese Perspective - Lai, Yung-Lien (International journal of offender therapy and comparative criminology, 2019)
This study draws on theories of importation and deprivation and relies upon self-reported survey data collected in 2015 from 1,045 committed juvenile offenders in Taiwan. Results drawn from Multinomial logistic regressions indicated that among the importation factors, gang membership, volatile temper, and precommitment victimization are significantly associated with violent misconduct. In regard to deprivation factors, longer term of commitment, higher levels of commitment stress, and victimization while committed dramatically increased the levels of violent misconduct, as expected. On the positive side, ongoing support from family and good staff relations significantly reduced the probability of engaging in violent behaviors while confined.